Borrowing credibility : global banks and monetary regimes - Grittersová, Jana (Michigan studies in international political economy., 2017)
"Nations with credible monetary regimes borrow at lower interest rates in international markets and are less likely to suffer speculative attacks and currency crises. While scholars typically attribute credibility to domestic institutions or international agreements, Jana Grittersová argues that when reputable multinational banks headquartered in Western Europe or North America open branches and subsidiaries within a nation, they enhance that nation's monetary credibility. These banks enhance credibility by promoting financial transparency in the local system, improving the quality of banking regulation and supervision, and by serving as private lenders of last resort. Reputable multinational banks provide an enforcement mechanism for publicized economic policies, signaling to international financial markets that the host government is committed to low inflation and stable currency. Grittersová examines actual changes in government behavior of nations trying to gain legitimacy in international financial markets, and teh ways in which perceptions of these nations change in relation to multinational banks. In addition to quantitative analysis of over 80 emerging-market countries, she offers extensive case studies of credibility building in the transition countries of Eastern Europe, Argentina in 2001, and the global financial crisis of 2008. Grittersová illuminates the complex interactions between multinational banks and national policymaking that characterize the process of financial globalization to reveal the importance of market confidence in a world of mobile capital."--Provided by publisher.